The Dominant Use of Requesting Language Function by Housekeeping Department Staff at Bintang Bali Resort - Made Puspanjali Artati; I Ketut Armawan; Ni Putu Era Marsakawati (Universitas Pendidikan Ganesha, 2025)
The limited variety and spontaneity of English expressions used by housekeeping department staff when interacting with guests at Bintang Bali Resort may affect the effectiveness of service communication. This study aims to analyse the dominant language functions used by housekeeping department staff and to describe their realisation through language expressions in daily service activities, based on the theoretical framework of Tillit and Bruder. The subjects of this study were four male housekeeping department staff members, consisting of a room attendant, a floor supervisor, and a runner, who are directly involved in guest service activities. This study used a descriptive qualitative method to obtain an in-depth picture of the use of language functions in the context of housekeeping work. Data collection techniques included direct observation, semi-structured interviews, and questionnaires. Data analysis was conducted qualitatively. The results of the study indicate that housekeeping department staff tend to use one main language function, namely the requesting function, which is realised through expressions of asking for permission, requesting assistance, offering services, apologising, and expressing gratitude. These expressions are mostly formulaic and follow the hotel's standard operating procedures to maintain politeness and professionalism in service. This study concluded that although housekeeping staff are capable of carrying out routine communication effectively, further language training is needed to improve spontaneous and adaptive communication skills to address diverse guest needs and characteristics. The implications of this research reinforce the concept that the use of language functions is strongly influenced by the work context and the speaker's communication needs.